(untitled) (CAHIERS MAGELLANES-NS, 2024)
Although postpartum depression (PPD) is prevalent and has significant negative impacts, there is currently no standardized screening program to identify affected mothers. Different Saudi Arabian cities have shown a varying PPD prevalence, with Riyadh being much higher. A translated version of the Edinburgh Postnatal Depression Scale (EPDS) was used to ascertain PPD prevalence in Jeddah. The Relative Importance Index (RII) was employed to evaluate the key indicators of PPD through the EPDS. The PPD prevalence rate was 39.5%, with no significant differences between age groups. The RII ranked first on the EPDS, which was related to patient happiness, was the most significant factor. Women in Jeddah demonstrated a high prevalence of PPD. We recommend organized screening programs to examine women during antenatal visits and the postpartum period for early intervention, management, and psychosocial support and to alleviate the negative impact of PPD. Postpartum depression (PPD) is a mood disorder classified under major depressive disorders, typically arising within four weeks to one year following childbirth. It is a crippling mental health issue that many new mothers face, affecting about 10–15% of adult mothers annually. It represents a substantial burden that affects the mother, the newborn, the family, and society as a whole. Although it might be expected for women in their postpartum period to experience feelings of sadness, fatigue, and mood swings due to hormonal fluctuations after childbirth, patients with PPD have dysphoric mood, hopelessness, anxiety, and fatigue, which affects the mother’s ability to function and attend to the infant’s basic needs such as breastfeeding and establishing an emotional bond. These symptoms may lead to feelings of guilt, shame, and isolation, potentially exacerbating the condition. In more extreme cases, affected women may develop harmful thoughts directed toward themselves or their infants. This might result in long-term effects on the child's cognitive, emotional, and social development.